Evaluating the Feasibility of Screening Relatives of Patients Affected by Nonsyndromic Thoracic Aortic Diseases: The REST Study - Riccardo Giuseppe Abbasciano; Giovanni Mariscalco; Julian Barwell; Gareth Owens; Mustafa Zakkar; Lathishia Joel‐David; Suraj Pathak; Adewale Adebayo; Nora Shannon; Rebecca Louise Haines; Hardeep Aujla; Bryony Eagle‐Hemming; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Diseases of the thoracic aorta are characterized by a familial etiology in up to 30% of the cases. Nonsyndromic thoracic aorta diseases (NS‐TADs) lack overt clinical signs and systemic features, which hinder early detection and prompt surgical intervention. We hypothesize that tailored genetic testing and imaging of first‐degree and second‐degree relatives of patients affected by NS‐TADs may enable early diagnosis and allow appropriate surveillance or intervention. Methods and Results We conducted a feasibility study involving probands affected by familial or sporadic NS‐TADs who had undergone surgery, which also offered screening to their relatives. Each participant underwent a combined imaging (echocardiogram and magnetic resonance imaging) and genetic (whole exome sequencing) evaluation, together with physical examination and psychological assessment. The study population included 16 probands (8 sporadic, 8 familial) and 54 relatives (41 first‐degree and 13 second‐degree relatives) with median age 48 years (range: 18–85 years). No syndromic physical features were observed. Imaging revealed mild‐to‐moderate aortic dilation in 24% of relatives. A genetic variant of uncertain significance was identified in 3 families. Imaging, further phenotyping, or a form of secondary prevention was indicated in 68% of the relatives in the familial group and 54% in the sporadic group. No participants fulfilled criteria for aortic surgery. No differences between baseline and 3‐month follow‐up scores for depression, anxiety, and self‐reported quality of life were observed. Conclusions In NS‐TADs, imaging tests, genetic counseling, and family screening yielded positive results in up to 1 out of 4 screened relatives, including those in the sporadic NS‐TAD group. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT03861741.